Farmers' knowledge, perceptions, and participation on the implementation of crop insurance program in Aceh Besar - Fadhliani, Z; Yustika, E; Nugroho, A; Hamid, A H (IOP conference series. Earth and environmental science, 2019)
The evaluation toward the implementation of crop insurance in Indonesia have been received relatively little attention. This study analyzes knowledge, perception and participation of farmers toward the implementation of the crop insurance program (AUTP) by using data from 80 subjects in Suka Makmur Subdistrict in the Regency of Aceh Besar. Utilizing a questionnaire, we display farmers' knowledge, perception, and participation reported based on frequencies. One-way ANOVA tests with the associated post-hoc tests, is performed to examine significant differences among means of knowledge, perception and participation levels with the independent variables being age, gender, education, household income, rice field area, and land ownership. The results indicate that only less than half of farmers have overall good knowledge, despite their participation in AUTP. Most of subjects respond relatively low level of participation toward AUTP. Knowledge, perception and participation levels are varied significantly based on the independent variables, but gender. In general, this study has shown farmers' low level of knowledge, perception and participation toward the implementation of AUTP crop insurance which can significantly affect the sustainability of the crop insurance program. Therefore, emphasis on the program to boost the level of knowledge, perception and participation of the farmers is needed.